2020
DOI: 10.1073/pnas.2002481117
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cGAS-mediated type I IFN responses in HIV-1–infected T cells

Abstract: The DNA sensor cGAS catalyzes the production of the cyclic dinucleotide cGAMP, resulting in type I interferon responses. We addressed the functionality of cGAS-mediated DNA sensing in human and murine T cells. Activated primary CD4+ T cells expressed cGAS and responded to plasmid DNA by upregulation of ISGs and release of bioactive interferon. In mouse T cells, cGAS KO ablated sensing of plasmid DNA, and TREX1 KO enabled cells to sense short immunostimulatory DNA. Expression of IFIT1 and MX2 was downregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 67 publications
8
26
0
Order By: Relevance
“…Thus, how Vpx impacts viral replication is very dependent on the nature of the assay, and the cells used. For example, during spreading infection in Jurkat T cells, which lack active SAMHD1 and cGAS, WT SIVmac and ∆vpx viruses replicate similarly, unless STING is activated with agonist (RR-S2 CDA), and then Vpx enhances infection, consistent with our data (28,33). The situation is certainly complex and incompletely understood.…”
Section: Vpx Blocks P65 Nuclear Translocationsupporting
confidence: 84%
“…Thus, how Vpx impacts viral replication is very dependent on the nature of the assay, and the cells used. For example, during spreading infection in Jurkat T cells, which lack active SAMHD1 and cGAS, WT SIVmac and ∆vpx viruses replicate similarly, unless STING is activated with agonist (RR-S2 CDA), and then Vpx enhances infection, consistent with our data (28,33). The situation is certainly complex and incompletely understood.…”
Section: Vpx Blocks P65 Nuclear Translocationsupporting
confidence: 84%
“…We and others previously reported that HIV-1 does not strongly induce innate immune responses, unless the virus is supplemented with accessory genes from other lentiviruses, carries structural or enzymatic mutations, or is treated with chemicals that alter its uncoating kinetics or interfere with its engagement with host factors [ 23 , 24 , 28 30 ]. We present here that ISG induction can occur when cells are challenged with excessively high virus concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, HIV-1 evades innate immune sensing in macrophages [ 54 , 55 , 56 ] and in CD4 T-cells [ 57 ]. Instability of the capsid core during reverse transcription was shown to trigger sensing of the viral DNA by cGAS in macrophages and monocytic-like THP-1 cells [ 58 ].…”
Section: Ca and Reverse Transcriptionmentioning
confidence: 99%
“…The triphosphohydrolase SAMHD1 has also been shown to reduce the interferon (IFN)-type 1 response triggered by the cGAS-STING pathway, presumably because fewer viral DNA molecules are synthesised when dNTPs concentration is lowered by SAMHD1 [ 59 ]. However, capsid destabilisation did not seem to trigger cGAS sensing in CD4 T-cells [ 57 ]. Moreover, it is worth noting that the viral DNA in purified RTCs seems quite resistant to nuclease digestion [ 34 , 60 ], and fully reverse-transcribed, integration-competent “pre-integration complexes” can be extracted from the cytoplasm of acutely infected cells [ 61 , 62 ], which suggests that sensing of viral nucleic acids may be suppressed by more than one mechanism.…”
Section: Ca and Reverse Transcriptionmentioning
confidence: 99%